ONYCHOMYCOSIS AND NAIL PSORIASIS - Moura Guedes da Costa Silva, Pedro Miguel (2015)
Psoriasis is a chronic disease, immune-mediated, affecting approximately 2% of the population. It results from a polygenic predisposition in combination with environmental factors, eg trauma, infection, or drugs. All forms of psoriasis may have nail involvement (40-45%), but sometimes this can occur alone (5%). Onychomycosis is an infection of the nail caused by dermatophytes, yeasts, or non-dermatophyte filamentous fungi; the most common agent is Trichophyton rubrum the (T. rubrum). It is still controversy regarding the higher or lower prevalence of onychomycosis in patients with psoriasis. Nail changes caused by psoriasis are sometimes clinically indistinguishable from those for onychomycosis, and we must make the differential diagnosis, because the treatment is different. There are several studies that analyze the possible predisposition of onychomycosis in patients with nail psoriasis and this literature review aims to analysis of these studies, published to date.